An unusual pathway of cardiac surgery repair of aortic and mitral valve – case report - Komorowski, Janusz; Moll, Maciej; Kopala, Marek (Prenatal Cardiology, 2020)
Prenatal diagnosis and the surgical treatment of the patient with complex aortic and mitral valve disease are rarely presented in scientific literature. At the 30th week of gestation a 34-year-old multigravida multipara was referred by a primary care obstetrician for a detailed ultrasound examination with a suspicion of complex aortic and mitral valve disease. The patient was born with critical aortic stenosis and mitral valve insufficiency and decreased left ventricular (LV) contractility due to endocardium fibroelastosis. On the second day of life the patient underwent balloon aortic valvuloplasty in the cath lab. At 3 months of age the patient underwent surgery. Mitral valve plasty and anterior left ventricular outflow tract (LVOT) incision were performed. At the age of 9 months the patient revealed circulatory insufficiency caused by mitral stenosis and recurrent insufficiency, and was qualified for implantation of a mechanical valve in the mitral position. Intraoperatively it was noted that mitral annulus was too small to implant a mechanical valve, so a biological valve was prepared with the CMx ECM on the operating table. The implantation of a CMx biological valve custom-made on the operating table was the bridge of surgical treatment for implantation of a mechanical valve in the future. The patient successfully underwent surgery. At 3 years old, we replaced the CMx valve with a mechanical St. Jude. This new pathway of cardiac surgery repairs in the first year of life might be an important issue for counselling parents-to-be after detection and diagnosis of prenatal congenital heart defects, such as in the presented case: abnormal aortic and mitral valve.